2015
DOI: 10.4081/ejh.2015.2513
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis activation in human carious dentin. An immunohistochemical study

Abstract: The exact mechanisms and enzymes involved in caries progression are largely unclear. Apoptosis plays a key role in dentin remodelling related to damage repair; however, it is unclear whether apoptosis in decayed teeth is activated through the extrinsic or the intrinsic pathway. This ex vivo immunohistochemical study explored the localization of TRAIL, DR5, Bcl-2 and Bax, the main proteins involved in apoptosis, in teeth with advanced caries. To evaluate TRAIL, DR5, Bcl-2 and Bax immunoexpressions twelve perman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Previous reports have shown that apoptosis is active in caries; furthermore, although fluoride can prevent caries, excessive fluoride intake can cause fluorosis. However, curcumin attenuates fluoride-mediated apoptosis through Akt activation and suppresses fluoride-mediated DNA damage [ 26 , 27 ]. Therefore, curcumin may reverse the apoptotic process caused by dental caries and excessive fluoride intake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have shown that apoptosis is active in caries; furthermore, although fluoride can prevent caries, excessive fluoride intake can cause fluorosis. However, curcumin attenuates fluoride-mediated apoptosis through Akt activation and suppresses fluoride-mediated DNA damage [ 26 , 27 ]. Therefore, curcumin may reverse the apoptotic process caused by dental caries and excessive fluoride intake.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, curcumin could decrease caries inflammation through MAPK1. BCL2 is a protein that regulates cell death and has been reported to be overexpressed in teeth with advanced caries [ 26 ]. However, it has also been reported that curcumin ameliorates bone loss by inhibiting osteoclastogenesis through several molecules, including BCL2 [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular matrix and hard tissues have become increasingly important topics, demonstrating that histochemistry may be suitably applied in particular to investigate cartilage or dentin during the histogenetic process 49-51 and in pathological conditions; 52 , 56 some papers were devoted to the temporomandibular joint in healthy and diseased subjects, 50 , 57-59 while other proposed in vitro models for chondrogenesis 60-62 or dentinogenesis. 63 Techniques for culture in vitro were also used for tissue engineering, using different supports for growing and differentiating various cell types: 64-67 Histochemistry thus proved to be an effective mean to characterize the structural and functional features of cells to be used for reconstructive medicine.…”
Section: The Last Five-years Record Of a Multidisciplinary Journal Ofmentioning
confidence: 99%